Democracy: Autonomos or Theonomos? - Briedis, Mindaugas (Problemos, 2006)
The notion of democracy, after a long history of transformation and rebirths from different sources, is so vast today that under this heading we can speak about prima facie incoherent values. The aim of the paper is not only to uncover some of the antinomies spreading from the paradoxical nature of democracy itself, but also to point the trajectories of possible solutions to these paradoxes. First we must realize the processual and ideal character of democracy. For these purposes, it is essential to analyze the basic notions and tensions accompanying democracy, which cannot be resolved appealing to logical (autonomy–heteronomy) or historical (Enlightenment–Romanticism) con troversies. The arguments for one or another side of these eventually lead to new forms of radical individualism or neocollectivism which does no good to the adaptability of democratic ideals in today’s world. After examining the implications of I. Kant’s moral philosophy for discussing democracy, we face P. Tillih’s thought which formulated the notion of theonomy as the answer to the negativity of autonomy and tensions regarding democracy and, moreover, strains between secular and religious spheres.